Corporate Entrepreneurship and Its Effect on Business Performance: Evidence from Digikala - Tajeddini, Omid; Tajdini, Javad (Springer, 2023)
This article examines the perspective of an intrapreneur aiming to provide valuable insights into the operations of an ecommerce website in their role as the firm's marketing manager. A research methodology using an inductive approach was used to examine the impact of corporate entrepreneurship (also known as intrapreneurship) on company performance in a challenging and unpredictable pandemic context. This methodology included using judgmental and convenient sampling approaches. The findings indicate that intrapreneurship and the employment of corporate websites and Instagram (a social platform) can influence the firm's overall success. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: E-commerce websites; Intrapreneur; Online stores; Pandemic